Effect of expectations and retention interval on prospective person memory and vigilance - Provenzano, Andrew C. (Psychology, crime & law, 2024)
The present research examined the role of expectations, delay and ongoing task on prospective person memory. Participants (N = 561) studied six mock missing person posters and were told that they had either a low chance or a high chance of encountering the missing persons. Participants were told to press the ‘h’ key if one of the persons was encountered. Participants engaged in a grocery store task immediately after studying the posters or after a five-minute delay. The grocery store task included photographs of 44 individuals, including one of the ‘missing persons’. During the grocery store task, participants either engaged in an attention demanding ongoing activity (i.e. looking for four items from a shopping list) or were able to devote themselves solely to looking for the missing persons. Expectations of encounter increased both correct and incorrect sightings, effects that were more pronounced after the five-minute delay. The presence of the ongoing task had no significant effect on sighting rates. Results are discussed in terms of the multiprocess model [McDaniel, M. A., & Einstein, G. O. (2000). Strategic and automatic processes in prospective memory retrieval: A multiprocess framework. Applied Cognitive Psychology, 14(7), S127–S144 .] and the preparatory attention and memory process model [Smith, R. E. (2003). The cost of remembering to remember in event-based prospective memory: Investigating the capacity demands of delayed intention performance. Journal of Experimental Psychology: Learning, Memory, and Cognition, 29(3), 347–361.] of prospective memory. We also discuss applications of these findings to missing person investigations.